Improving the brand identity of time-honored Chinese brand through visual innovative design - Fan, Xinying; Ismail, Adzrool Idzwan bin (International Journal of Management and Sustainability, 2024)
The purpose of this study is to explore the role of visual innovation design in brand identity with time-honored Chinese brands. Traditional design and innovative design are two inherent attributes of visual design for time-honored Chinese brands. Different visual design approaches have varying effects on brand identity, thus necessitating research on the impact of brand visual design on brand identity. This paper employs quantitative research by conducting a survey among 566 consumers from different age groups. The empirical results indicate that the traditional design of time-honored Chinese brands does not significantly influence brand identity, whereas innovative design does impact brand identity for these brands. This study highlights the importance for time-honored Chinese brands to pay attention to the role of innovative visual design in responding to changing consumer demands and addressing the issue of brand aging. Only by doing so can they effectively manage their brands and achieve long-term development. Therefore, it is recommended that brand managers or relevant departments of time-honored Chinese brands utilize innovative visual designs with elements of tradition during brand promotion to attract more consumers and achieve sustainable growth. This study also promoted the in-depth development of research on consumer culture, corporate culture, and brand cultural heritage management.